KNOWLEDGE AND ATTITUDES TOWARD PEOPLE WITH DEMENTIA AMONG NURSING STUDENTS IN YOGYAKARTA, INDONESIA - Salsabilla Rohadatul ‘Aisy Sunaryo; Azam David Saifullah; Sri Mulyani (Belitung Raya Foundation, Indonesia, 2020)
Background: Nursing students are prepared to deliver care for vulnerable people, including people with dementia. Nursing students tend to have lower levels of knowledge and attitudes toward dementia compared to registered nurses. While there is less evidence that discussed this topic in the Indonesian nursing student's context, it will be necessary to identify an aspect related to knowledge and attitude among students to be considered for improvement in the future. Objective: This study aimed to identify the knowledge and attitudes toward dementia among nursing students in Indonesia. Method: This study was a quantitative study with a cross-sectional design. There were 334 nursing students recruited using a total sampling method at Universitas Gadjah Mada, Yogyakarta. Data were collected using the Dementia Knowledge Assessment Scale (DKAS) and Dementia Attitude Scale (DAS). Spearman Rank, Mann Whitney Unpaired, Kruskal-Wallis test, Pearson Correlation, Unpaired t-test, and Unpaired ANOVA were used for data analysis according to the type and the distribution of the data. Results: The median of the DKAS was 24 (min - max = 7 - 40), and the mean of DAS was 99.60 (SD = 10.25). The variables that were statistically significant correlated to knowledge of dementia were age (r = .332, p < .001), class standing (H = 72.253, p < .001), and experience in taking care of people with dementia (U = 3314, p = .047). Meanwhile, only the age of the students was found to have a statistically significant correlation with attitudes toward dementia (r = 158, p = .004). Conclusion: In general, among the nursing students, knowledge toward dementia was relatively low, while the attitudes toward dementia were relatively high compared to other research. Age, class standing, and experience in taking care of people with dementia had significant correlations to the knowledge score of the students. Lastly, age also had a significant correlation with the attitude score of the students.